Clear Cell Urothelial Carcinoma: A Study of 10 Cases and Meta-Analysis of the Entity. Evidence of Mesonephric Differentiation. (February 2017) - Mai, Kien T.; Bateman, Justin; Djordjevic, Bojana; Flood, Trevor A.; Belanger, Eric C.
Clear cell urothelial carcinoma (CCUC) is a rare variant of urothelial carcinoma (UC) and its clinical significance has not been well elucidated. Consecutive cases of UC over a period of 5 years were reviewed. Histopathological tumor parameters, including the proportion of tumor cells with clear cell change, and patient outcomes were recorded. Expression of the following immunohistochemical markers was investigated: CK7, CK20, CK5, CD44, and PAX8. We also conducted a review of the literature for case reports/series of CCUC. Ten CCUCs were identified out of a total of 872 cases of UC. The clear cell component was characterized by prominent cytoplasmic membranes and voluminous clear cytoplasm, and accounted for 30% to 90% of the invasive tumor component. Of all the non-CCUC cases reviewed, at least 50% (noninvasive or invasive UC) showed focal areas of clear cell change that accounted for less than 5% of the neoplastic cells. Immunohistochemically, CCUC exhibited positive reactivity for CK5/CD44 (n = 9); CK20 (n = 5), PAX8 (very focal to extensive) (n = 6), and GATA3/CK7 (n = 10). Eight of 10 CCUC were of advanced clinical stage (pT3/pT4) and 6 of 10 experienced tumor recurrence and/or death due to disease. In conclusion, CCUC can be distinguished from non-CCUC by the extensive clear cell change in more than 30% of cells. This variant is associated with rapid progression to muscle invasion and metastasis, with an aggressive clinical course. Expression of CK5/CD44 may represent basal cell features in most CCUC cases, while PAX8 expression is suggestive of mesonephric derivation.